Necropsy Findings, Isolation and Identification of Salmonella pullorum in Layer Chickens in Sumedang, Indonesia: A Case Report - Maharani, Briliant; Cyntia, Annisa Permata; Azra, Putri Zivana; Hartady, Tyagita; Windria, Sarasati; Prayugo, Armanda Dwi (Jurnal Veteriner, 2026)
Pullorum disease or Chalky feces, caused by Salmonella pullorum bacteria, is a highly contagious bacterial infection that significantly affects commercial poultry, particularly in developing countries. This study was aimed to report a case of pullorum disease in commercial layer chickens in Sumedang, West Java, Indonesia. The diagnostic approach included clinical examination based on clinical signs, followed by pathological and microbiological identification. Clinical signs observed were lethargy, white diarrhea (chalky feces) and decreased egg production. Necropsy findings revealed pathological changes including hepatomegaly, splenomegaly, caseous masses in the caecum and joints, oophoritis and white nodules in the heart. Additional anatomy pathological findings included tracheal hyperemia and malacia in the brain. Bacterial isolation and identification were conducted from internal organs using MacConkey Agar, followed by Gram staining and biochemical tests including Kligler’s Iron Agar (KIA), Motility Indole Urea (MIU) and Simmons’s Citrate Agar. The results confirmed the presence of S. pullorum bacteria, characterized by non-motile, Gram-negative bacilli. These findings demonstrate that S. pullorum can cause systemic infection affecting multiple organs. Based on pathological and microbiological examinations, it was concluded that the disease case in the layer chicken samples was caused by chronic infection of S. pullorum. This report highlights the importance of early diagnosis and improved biosecurity measures to prevent outbreaks, reduce mortality rates and minimize economic losses in Chicken farming.